2002
DOI: 10.1001/archotol.128.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Underexpression of p27/Kip in Thyroid Papillary Microcarcinomas With Gross Metastatic Disease

Abstract: Our results suggest that p27 immunohistochemical analysis may be a valuable diagnostic tool in predicting aggressive potential in PMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…[19][20][21] Our data showed that cyclin D1 expression is associated with lymph node metastasis, but not with macrometastasis or lateral node metastasis. And it failed to be independent predictive factor for lymph node metastasis, probably because of its strong association with tumor size (Po0.001).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…[19][20][21] Our data showed that cyclin D1 expression is associated with lymph node metastasis, but not with macrometastasis or lateral node metastasis. And it failed to be independent predictive factor for lymph node metastasis, probably because of its strong association with tumor size (Po0.001).…”
Section: Discussionmentioning
confidence: 56%
“…However, to our knowledge, there have been few studies of the predictive factors for lymph node metastasis in papillary microcarcinomas, except for expression of cyclin D1 and p27, which were reported to be associated with lymph node metastasis. [19][20][21] In the present study, we investigated the predictive factors of lymph node metastasis in a large series of papillary microcarcinomas by analyzing clinicopathological variables, including patient age, tumor size (Z5 vs o5 mm), extrathyroidal extension, multifocality, histological subtype, sclerosis and encapsulation, expression of S100A4, cyclin D1, p27 and MUC1 and presence of the BRAF V600E mutation.…”
mentioning
confidence: 99%
“…The BRAF V600E mutation has been shown to be associated with aggressive clinical behaviors of PTC by some investigators [37]; however, the evidence is still inconclusive, with contradictory reports [38]. Other molecular markers being investigated include cell-cycle regulators p27, p21, and cyclin D1 and immunohistochemical markers such as CEACAM-1 (carcinoembryonic antigenrelated cell adhesion molecule 1), OPN (osteopontin), and E-Cadh (E-cadherin) [39,40]. None of these markers have reached wide acceptance in clinical practice so far, including BRAF.…”
Section: Microrna In Staging and Prognosticationmentioning
confidence: 99%
“…We also investigated p27 expression in this group of microcarcinomas and found it to be expressed in 63.4% of cases, confi rming the previously described fi nding that lymph node metastases showed a statistically signifi cant correlation with cyclin D1 expression and p27 non-expression (p=0.093) (Table 3). Similarly, Khoo et al report on a decreased level of p27 expression in papillary microcarcinomas with lymph node metastases as compared with those without lymph node metastases 27 . Th ese results confi rmed the importance of evaluating p27, cyclin D1 and RET expression, suggesting their potential usefulness in the evaluation of microcarcinoma behavior.…”
Section: Discussionmentioning
confidence: 84%